2016
DOI: 10.1038/oncsis.2016.1
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-125a promotes paclitaxel sensitivity in cervical cancer through altering STAT3 expression

Abstract: Cervical cancer (CC) is one of the most common malignancies in women. Paclitaxel is the front-line chemotherapeutic agent for treating CC. However, its therapeutic efficacy is limited because of chemoresistance, the mechanism of which remains poorly understood. Here, we used microRNA (miRNA) arrays to compare miRNA expression levels in the CC cell lines, HeLa and CaSki, with their paclitaxel resistance counterparts, HeLa/PR and CaSki/PR. We demonstrate that miR-125a was one of most significantly downregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 42 publications
4
50
0
2
Order By: Relevance
“…It has been reported that STAT3 signaling pathway is participated in lung cancer cell proliferation and survival, 47 and STAT3 is also known to involve in cell apoptosis of cervical cancer and glioma. 48,49 Our data also demonstrated that miR-9600 overexpression resulted in decreased expression of STAT3 and then led to cell apoptosis or survival in NSCLC ( Figure 7 ). In the present study, we first focused on cell growth and apoptosis and evaluated the functions of miR-9600 on the downstream genes of the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It has been reported that STAT3 signaling pathway is participated in lung cancer cell proliferation and survival, 47 and STAT3 is also known to involve in cell apoptosis of cervical cancer and glioma. 48,49 Our data also demonstrated that miR-9600 overexpression resulted in decreased expression of STAT3 and then led to cell apoptosis or survival in NSCLC ( Figure 7 ). In the present study, we first focused on cell growth and apoptosis and evaluated the functions of miR-9600 on the downstream genes of the STAT3 signaling pathway.…”
Section: Discussionsupporting
confidence: 57%
“…48,49,50 Our data also showed that miR-9600 modulates cell motility and metastasis in A549 and SPC-A-1 cells by targeting the STAT3 gene ( Figure 6 ). In addition, miR-9600 expression repressed tumorigenesis in vivo , evidenced by the fact that both mice injected with miR-9600 and si-STAT3 exhibited a decreased tumorigenesis in comparison to the NC- and ASO-9600-injected mice.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…STAT3 with high degrees of phosphorylation do not exist in normal ovarian epithelial cells lines or benign ovarian tumor cell lines, and abnormal activation of the STAT3 signal transduction pathway may induce a malignant phenotype (23). Previous studies investigating the downstream target gene of the STAT3 transduction pathway have provided increasing evidence, which suggested that the STAT3 transduction pathway serves an important role in a number of processes, including overproliferation, inhibition of apoptosis, vascular reconstruction, invasion and metastasis and drug resistance (24).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other miRNAs, such as miR-106a [278, 279], miR-130b [280], miR-134 [281], miR-145 [282], miR-149 [283], miR-186 [284], miR-197 [285], miR-429 [286], miR-433 [287], miR-490 [288] and miR-591 [278] have been linked to paclitaxel and/or cisplatin resistance in OC. miR-125a [289], miR-224 [290] and miR-375 [291, 292] expression has been linked with paclitaxel resistance in CC cells. Interestingly, although a reduced expression of miR-31 was observed to correlate with paclitaxel resistance [255], its over-expression was reported to drive cisplatin resistance [293].…”
Section: Biological Significance Of Mirnas In Gynecologic Cancersmentioning
confidence: 99%